2019
DOI: 10.1186/s13018-019-1093-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive spinopelvic “crab-shaped fixation” for unstable pelvic ring fractures: technical note and 16 case series

Abstract: Background Unstable sacral fractures are high-energy injuries and comprise polytrauma. Internal fixation to enable withstanding vertical loads is required to get up early from the bed after an unstable sacral fracture. We developed a new minimally invasive surgical (MIS) procedure for unstable pelvic ring fractures and reported it in Japanese in 2010. We presented our minimally invasive surgical technique of crab-shaped fixation for the treatment of unstable pelvic ring fractures and report on its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…Toda et al reported a mean surgical time of 129 minutes with an intraoperative blood loss of 223 ml for posterior pelvic-ring stabilization in unstable pelvic ring fractures using the transiliac rod and screw xation technique 7 . Similar results were reported by Okuda et al (158 minutes and 299 ml using the crab-shaped xation technique) 8 . These surgical techniques are less invasive than conventional ORIF but are still highly invasive for frail patients.…”
Section: Discussionsupporting
confidence: 90%
“…Toda et al reported a mean surgical time of 129 minutes with an intraoperative blood loss of 223 ml for posterior pelvic-ring stabilization in unstable pelvic ring fractures using the transiliac rod and screw xation technique 7 . Similar results were reported by Okuda et al (158 minutes and 299 ml using the crab-shaped xation technique) 8 . These surgical techniques are less invasive than conventional ORIF but are still highly invasive for frail patients.…”
Section: Discussionsupporting
confidence: 90%
“…Posterior fixation of unstable pelvic ring injuries using spinal instrumentation brings good reduction and strong stability [ 7 , 8 ]. Recently, minimally invasive posterior fixations of unstable pelvic ring injuries using spinal instrumentation have been reported and show good clinical results [ 9 , 10 ]. Because these techniques require screw insertion into the ilium, cases of pelvic ring injury with iliac fracture cannot be treated using these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Ebata et al [20] applied spinal-pelvic xation system in adult spinal deformity correction and achieved satisfactory results. Futamura et al [21], Koshimune et al [22], Okuda et al [23] used small incision minimally invasive lumbo-iliac xation to reduce the risk of skin and soft tissue injury and infection, and improve the healing rate of fracture. Song et al [24] compared the biomechanical characteristics between bilateral and unilateral lumbo-iliac xation in unilateral comminuted sacral fractures by nite element analysis and the results revealed that the stability of unilateral lumbo-iliac xation is insu cient to reconstruct the posterior pelvic ring.…”
Section: Discussionmentioning
confidence: 99%